Zero to One: Note on Start Ups, or How to Build the Future - Thiel, Peter; Masters , Blake; Aneet , (Gyan Management Journal, 2017)
In the words of Peter, this book (or better to say a compilation of notes) is about how to build companies that create new things. Personally, I would say this book gives a good window into the mind of a great entrepreneur like Peter, which may give solace to other entrepreneurs with out of box idea and who are not getting support from near quarters. This is not a book which will detail out the steps in the journey, but it can tell you about what to expect in the journey. And nothing about the destination - that is for each to define as their own.
Keywords: compilation; companies; Personally; entrepreneur; Peter